An empirical model of the high‐energy electron environment at Jupiter. Issue 10 (19th October 2016) - de Soria‐Santacruz, M.; Garrett, H. B.; Evans, R. W.; Jun, I.; Kim, W.; Paranicas, C.; Drozdov, A.
Abstract: We present an empirical model of the energetic electron environment in Jupiter's magnetosphere that we have named the Galileo Interim Radiation Electron Model version‐2 (GIRE2) since it is based on Galileo data from the Energetic Particle Detector (EPD). Inside 8 R J, GIRE2 adopts the previously existing model of Divine and Garrett because this region was well sampled by the Pioneer and Voyager spacecraft but poorly covered by Galileo. Outside of 8 R J, the model is based on 10 min averages of Galileo EPD data as well as on measurements from the Geiger Tube Telescope on board the Pioneer spacecraft. In the inner magnetosphere the field configuration is dipolar, while in the outer magnetosphere it presents a disk‐like structure. The gradual transition between these two behaviors is centered at about 17 R J . GIRE2 distinguishes between the two different regions characterized by these two magnetic field topologies. Specifically, GIRE2 consists of an inner trapped omnidirectional model between 8 to 17 R J that smoothly joins onto the original Divine and Garrett model inside 8 R J and onto a GIRE2 plasma sheet model at large radial distances. The model provides a complete picture of the high‐energy electron environment in the Jovian magnetosphere from ∼1 to 50 R J . The present manuscript describes in great detail the data sets, formulation, and fittings used in the model and provides a discussion of the predicted high‐energy electron fluxes as a function of energy and radial distance from the planet. Key Points: Presented a model of the high‐energy electron environment in the magnetosphere of Jupiter based on data from the Galileo EPD instrument The model distinguishes between two different regions characterized by two magnetic field topologies Radial electron flux profiles show enhanced regions of radiation and compare reasonably well with the JOSE model